ENVIRONMENTAL IMPACT OF MANUFACTURING ENTERPRISES - Samadova Kh. S. (American Journals, 2024)
People have always been closely connected with nature, but it is not difficult to see how this connection disappears and disappears with time. An example of human alienation from nature is the process of industrialization of countries. The process of industrialization is the transition from traditional society to industry, from manual labor to mechanical engineering.
Keywords: Environment, waste, harmful gases, industry, manufacturing enterprises.